Positive Solutions of Fully Nonlinear Elliptic Equations on General Bounded Domains (Journal of Partial Differential Equations, 2001)
We prove the refined ABP maximum principle, comparison principle, and related existence and uniqueness theorem for the positive solutions of the Dirichlet problems of second order fully nonlinear elliptic equations on arbitrary bounded domains.
Keywords: Refined ABP maximum principle; fully nonlinear equation; arbitrary bounded domain